Pengaruh Budaya Organisasi Dan Motivasi Terhadap Kepuasan kerja Pegawai di Kecamatan Tulung Klaten - Arman, Gian Aulia; Herawati, Jajuk (Universitas Muhammadiyah Metro, 2022)
this study aims to determine how the level of organizational culture and motivation on job satisfaction in Tulung Klaten sub-district. The research model used is a quantitative descriptive research model, which means that the sample is taken based on a certain number in a population. In this study the population used is the entire population. There are 50 staff in the Tulung Klaten sub-district. The sample used is also 50 respondents consisting of echelon officials to administrative staff in the Tulung sub-district. The data processing method used is the SPSS version 23 application.The data used are multiple linear regression analysis, classic assumption test, hypothesis test, determination coefficient test and simultaneous f test. The results of this study state that there is a positive and significant effect of Organizational Culture on Job Satisfaction of Employees of Tulung Klaten District, There is no significant effect on Motivation And Job Satisfaction of Employees of Tulung Klaten District and Simultaneously there is a positive and significant influence between Organizational Culture and Motivation on Job Satisfaction of Employees of Tulung Klaten Subdistrict Keywords : Organizational Culture, Motivation, Job Satisfaction